Staging an International Rock Festival in Alberta: A Documentary Reconstruction of Edmonton’s Rock Cirkus - Silversides, Brock (CAML Review / Revue de l'ACBM, 2017)
This paper, delivered in a shortened form at the CAML Conference in Calgary in June 2016, details the lead up to and production of the Edmonton Rock Cirkus in August 1979. It was the largest outdoor rock festival held in the Alberta capital up to that time, and was successfully staged in Commonwealth Stadium with a combination of top name international and Canadian acts, such as Peter Frampton, Heart, Streetheart, and Trooper. Using a combination of archival documents (primarily from the Martin Melhuish Fonds, held by Media Commons at the University of Toronto), contemporary press accounts, and reminiscences by organizers and performers, the groundbreaking festival's background, organization, logistics, economics, and physical production are reconstructed and discussed.